Dog-Assisted Therapy in Neurorehabilitation of Children with Severe Neurological Impairment: An Explorative Study - Hediger, Karin; Boek, Friederike; Sachers, Julia; Blankenburg, Ulrike; Antonius-Kluger, Evelyn; Rist, Bettina; Schaudek, Martina; Staudt, Martin; Kluger, Gerhard (Neuropediatrics, 2020)
Background Dog-assisted therapy (DAT) is increasingly applied in neurorehabilitation of patients with severe neurological impairments. To date, there are only anecdotal reports investigating its effects.Objectives This study was aimed to evaluate the potential of DAT in pediatric inpatient neurorehabilitation for severely neurologically impaired children and adolescents, to identify characteristics of patients receiving this therapy, characteristics of the therapy sessions, and to evaluate feasibility and extent of goal achievement.Methods We retrospectively analyzed 850 DAT sessions performed between 2010 and 2017 at an inpatient neurorehabilitation center. The dataset included 196 children and adolescents (Md = 5.50, 0.58–20.33 years) suffering from severe neurological impairments (disorders of consciousness in 37 patients) of various etiologies. We extracted information regarding patient and session characteristics, analyzed the predefined goals with content analysis, and examined to what extent the goals were met during DAT. Data were analyzed using descriptive statistics.Results Patients received an average of 4.34 therapy sessions. A total of 247 of 392 predefined goals (63%) were reached during DAT. The most frequently achieved goal was “enhancing fun” (83%), followed by “establishing contact and communication” (81%), and “relaxation” (71%). Only one critical incident regarding the dogs' safety occurred.Conclusion DAT is a feasible approach and appears to facilitate emotional, social, and psychological goals in children and adolescents with severe neurological impairment.
Keywords: animal-assisted therapy; dog-assisted therapy; neurorehabilitation; child; dog